# Formally how does one show that if $\Sigma$ is consistent and $\Sigma \vdash p$ then $\Sigma \cup \{ p\}$?

I think intuitively its obvious. If we have a collection of sentences that never proved $$\bot$$ and we add a new sentence that proves $$p$$, there should be no reason that the new set of proposition/assumptions becomes inconsistent (i.e. proves bottom or proves $$\neg p$$).

However, I assume this has to actually be shown to be true using propositional axioms or something else. Note that this is only interesting if we have not already proved the completeness theorem. Otherwise the solution is simple:

Since we have by assumption that $$\Sigma \vdash p$$ then it must be $$\Sigma \models p$$ (every model of $$\Sigma$$ makes p true). Therefore, since models are defined by truth function (in propositional logic at least) and functions are defined such that:

$$t(p) = 1 \iff t(\neg) = 0$$

it must mean that $$t(\neg) = 0$$. Which shows $$\Sigma \not \models \neg p$$ which again using the completeness theorem means $$\Sigma \not \vdash \not p$$. Since only having $$\neg p$$ and $$p$$ leads to $$\bot$$ it must be that we can't prove $$\bot$$ and therefore the new system $$\Sigma \cup \{ p \}$$ is consistent.

Without that, how do we show that true?

Note this is Corollary 2.2.9 on page 22 of these notes so I assume we can only use knowledge up to that corollary.

As a reference here are the propositional axioms:

1. T
2. $$\varphi \to (\varphi \lor \psi); \varphi \to (\psi \lor \varphi)$$
3. $$\neg \varphi \to (\neg \psi \to \neg (\varphi \lor \psi)$$
4. $$(\varphi \land \psi) \to \varphi; (\psi \land \varphi) \to \psi$$
5. $$\varphi \to (\psi \to (\varphi \land \psi))$$
6. $$(\varphi \to (\psi \to \theta)) \to ((\varphi \to \psi)\to (\varphi \to \theta))$$
7. $$\varphi \to (\neg \varphi \to \bot)$$
8. $$(\neg \varphi \to \bot) \to \varphi$$

and the completeness theorem I used:

1st form:

$$\Sigma \vdash p \iff \Sigma \models p$$

By the cut rule (or the cut theorem depending on the formal proof system under consideration), if we had $$\Sigma \vdash p$$ and $$\Sigma \cup \{ p \} \vdash \bot$$ then it would follow that $$\Sigma \vdash \bot$$.
• In a Hilbert-style system, the proof of the cut theorem is essentially that you can "concatenate" the two proofs, taking the $\Sigma \vdash p$ proof first and then the $\Sigma \cup \{ p \} \vdash q$ proof second. The only slightly tricky part is in applying the "assumption" rule in the second part - then either the assumption is from $\Sigma$ in which case it's OK, and otherwise it's $p$ which you can recast as "repeat previous step" - or if that's technically not allowed, expand it to a proof of $p \rightarrow p$ followed by applying modus ponens on $p \rightarrow p$ and previous step $p$. Oct 10, 2018 at 19:17
• (The previous comment is for the general version $\Sigma \vdash p$ and $\Sigma \cup \{ p \} \vdash q$ implies $\Sigma \vdash q$.) Oct 10, 2018 at 19:19